Cultural proximity: A source of trade flow resilience?. (23rd April 2018) - Carrère, Céline; Masood, Maria
Abstract: While the significant influence of cultural proximity on bilateral trade flows has been extensively documented in the literature, its possible role in times of crisis has not yet been raised. Relying on a panel estimation of a gravity model incorporating cultural proximity parameters, we evidence the existence of a significant surge in the impact of the different components of cultural proximity during economic recession. The trade resilience among countries sharing a cultural bond is not a pure composition effect as it also appears within product categories. To understand this unexpected effect, we discuss different mechanisms that emphasise the potential mitigating influence of cultural proximity on some determinants of the trade collapse, namely the uncertainty shock, the increased moral hazard and the emergence of ethnocentric preferences.